2014
DOI: 10.1126/science.1257377
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of closed magnetic flux trapped in the high-latitude magnetosphere

Abstract: Abstract:The structure of Earth's magnetosphere is poorly understood when the interplanetary magnetic field is northward. Under this condition, uncharacteristically energetic plasma is observed in the magnetotail lobes, which is not expected in the textbook model of the magnetosphere. Using satellite observations, we show that these lobe plasma signatures occur on high latitude magnetic field lines that have been closed by the fundamental plasma process of magnetic reconnection. Previous authors have suggested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
115
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 51 publications
(138 citation statements)
references
References 37 publications
21
115
2
Order By: Relevance
“…As more and more flux is closed in this magnetic local time (MLT) sector, the trapped field lines will protrude deeper into the magnetotail lobes. This mechanism has been validated by several different case studies [e.g., Goudarzi et al , ; Fear et al , ]. Furthermore, the main predictions from the mechanism, i.e., a delay in the MLT dependence on the IMF B y and an association with TRINNI flows, have been statistically verified by Fear and Milan [, ].…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…As more and more flux is closed in this magnetic local time (MLT) sector, the trapped field lines will protrude deeper into the magnetotail lobes. This mechanism has been validated by several different case studies [e.g., Goudarzi et al , ; Fear et al , ]. Furthermore, the main predictions from the mechanism, i.e., a delay in the MLT dependence on the IMF B y and an association with TRINNI flows, have been statistically verified by Fear and Milan [, ].…”
Section: Introductionmentioning
confidence: 63%
“…These features are more consistent with the DMSP precipitation associated with the dawnside arcs in this study. Fear et al [] also presented observation from Cluster that showed that the plasma source for this arc was on closed field lines. Similarly, a study by Mailyan et al [] presented observations of a transpolar arc (observed by IMAGE and the TIMED/GUVI instrument, which is very similar to SSUSI) and a conjugate in situ plasma signature detected by Cluster.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As lobe reconnection is distinct in each hemisphere, the motion of the TPA in one hemisphere is anticipated to be independent from the motion of the TPA in the opposite hemisphere. A recent case study of a TPA [ Fear et al ., ], observed during a conjunction with the Cluster spacecraft, has demonstrated that closed magnetic flux is observed at high altitudes in the magnetotail, which moves to and fro as predicted by the Milan et al [] mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…It was first suggested by Frank et al [] that the plasma sheet would be bifurcated, where the bifurcated tongue maps high into the lobes and to a theta aurora in the middle of the polar cap. Observation of filamentary plasma sheet extensions into the lobes during a transpolar arc event [ Huang et al, ] and recent observations of closed field lines filled with atypically hot plasma within the lobes [ Fear et al, ] during a transpolar arc event shows that such a plasma sheet topology may exist.…”
Section: Introductionmentioning
confidence: 99%